SAT0481 Early Detection and Treatment for Borderline Pulmonary Arterial Hypertension in Patients with Systemic Sclerosis in Japan. (9th June 2015) - Kawaguchi, Y.; Takagi, K.; Tochimoto, A.; Higuchi, T.; Yamanaka, H.
Abstract : Background: Pulmonary arterial hypertension (PAH) is one of life-threatening complications in patients with systemic sclerosis (SSc). The gold standard of diagnosing PH is using right heart catheterization. Recently, DETECT study (1) was published and showed the first evidence-based detection algorithm for PAH in SSc. This algorithm was composed by eight parameters including anti-centromere antibody, telangiectasia, %FVC/%DLco, uric acid, NT-proBNP and right axis deviation of ECG. However, anti-centromere antibody and telangiectasia have not been associated with PAH with SSc in the Japanese population. It would be necessary to establish an algorithm for detecting early stage PAH in Japan. In the treatment of SSc-associated PAH, the survival rate is still low compared to idiopathic PAH and non-SSc-PAH. Objectives: Our aim is to determine a new method for the detection of early PAH in patients with SSc in Japan. And then, we investigate the predicative values of a new algorithm using the results of right heart catheterization. The second aim is to determine the efficacy of PAH-specific therapy for borderline PAH. Methods: We enrolled 118 consecutive patients with SSc in this study, who were admitted to our University Hospital between 2005 and 2014. At first, echocardiography was performed in all patients, and if estimated right ventricular systolic pressure (eRVSP) was more than 40 mmHg, serum levels of NT-pro BNP and %DLco were estimated. If NT-proBNP was more than 250 pg/ml or %DLco was less than 60%, we recommended the patient should be performed by right heart catheterization. Results: As a result of screening 118 patients by the algorithm, 29 patients (25%) were recommended to undergo right heart catheterization and they were accepted to the examination. Consequently, mean pulmonary artery pressure (mPAP) of 10 patients was 25 mmHg or more, and they were diagnosed as a PAH. Eleven patients showed less than 20 mmHg of mPAP which was normal mPAP. And then, 8 patients showed a borderline mPAP between 21 and 24 mmHg of mPAP. We treated them with PAH-specific drugs; bosentan, sildenafil, tadalafil, and beraprost. After 1 year from treatment, all 8 patients underwent the second right heart catheterization. The levels of mPAP were less than 20 mmHg in all of 8 patients. In addition, the levels of NT-pro BNP decreased to the normal levels. Conclusions: A new algorithm for the early detection of PAH in patients with SSc could detect 35% of manifest PAH, and 28% of borderline PAH. If patients with borderline PAH were started to be treated with PAH-specific therapy, their mPAP could be improved to the normal range. References: Coghlan JG, Denton CP, Grunig E, et al. Evidence-based detection of pulmonary arterial hypertension in systemic sclerosis: the DETECT study. Ann Rheum Dis 2014;73:1340-1349 Disclosure of Interest: None declared